Study of Perception of Leadership Effectiveness in Relation to Institutional Effectiveness and Gender of the Teachers - Gifty Arora, Amit Kauts, Bharati Rani, Babudhan Tripura, M Sowjanya (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This study's major goal was to investigate the connection between teachers' gender, institutional effectiveness, and perceptions of leadership effectiveness. A total of 174 schools were chosen for data collection, and of these, 47 met Kelley's criteria for high effectiveness and 47 did not. Ten instructors who instruct the Xth grade from each school were randomly chosen as a sample. Data were gathered using two tools, the Institutional Effectiveness Scale (created by the researcher) and the Leadership Effectiveness Scale (Taj, 2010). The study found a substantial difference between high- and low-effective institutions in the perception of leadership effectiveness. The perception of leadership effectiveness between male and female instructors also showed a substantial difference, with female teachers seeing it more favorably than male teachers. The impact of institutional effectiveness and teacher gender on students' assessments of the effectiveness of their leaders, however, was not determined to be significant.